1984
DOI: 10.1007/bf01003394
|View full text |Cite
|
Sign up to set email alerts
|

Staining of proteoglycans in mouse lung alveoli. II. Characterization of the Cuprolinic Blue-positive, anionic sites

Abstract: The nature of Cuprolinic Blue-positive anionic filaments in mouse lung alveoli has been characterized. The contrast of filaments in the alveolar basement membrane of type I epithelial cells was lost on treatment with nitrous acid and pronase (without prefixation). In contrast, neither neuraminidase, chondroitinase ABC or AC, nor Streptomyces hyaluronidase had any effect. Treatment with pronase (after prefixation) and 2.0 M MgCl2 (after prefixation) also had no effect, indicating that the filaments are heparan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The GAGs are powerful inhibitors of proteases, including leucocyte elastase [20,22,53], and prevent leucocyte elastaseinduced emphysema in mouse and rat [23,24]. Ultrastructurally, proteoglycans are present around collagen fibrils, elastin fibres and in basement membranes [6,25,27,28]. Removal of proteoglycans associated with elastin facilitates the digestion of the latter [54][55][56].…”
Section: Lung and Urinary Gag Content After Elastase Instillationmentioning
confidence: 99%
See 1 more Smart Citation
“…The GAGs are powerful inhibitors of proteases, including leucocyte elastase [20,22,53], and prevent leucocyte elastaseinduced emphysema in mouse and rat [23,24]. Ultrastructurally, proteoglycans are present around collagen fibrils, elastin fibres and in basement membranes [6,25,27,28]. Removal of proteoglycans associated with elastin facilitates the digestion of the latter [54][55][56].…”
Section: Lung and Urinary Gag Content After Elastase Instillationmentioning
confidence: 99%
“…In addition, the close association of PGs with structural elements in the alveolar wall (e.g. basement membranes, collagen fibrils and elastin fibres) indicates a protective role [6,[25][26][27][28].…”
mentioning
confidence: 99%
“…Growth factors like fibroblast growth factors are retained by HS. Electron microscopical studies using cationic probes indicate that HS in the basement membranes of alveolar type I and type II cells and of alveolar endothelial cells are differentially sulfated (12,13). Sulfated proteoglycans play a central role in the modulation of the extracellular matrix of pulmonary fibroblasts, and HSPGs are involved in neutrophil trafficking to the alveolar space (14).…”
mentioning
confidence: 99%
“…(1989) concluded that without the use of an agent to preserve the highly aqueous soluble negativelycharged glycoconjugates, more than 50% of these macromolecules are lost from the tissue during histochemical processing. However, in this study as in numerous other studies (Van Kuppevelt et al, 1984b;Haigh & Scott, 1986;V61ker et aL, 1986;Velasco & Hidalgo, 1988;Sauren et aL, 1989), chondroitinase digestions were performed on samples pre-fixed in aldehyde alone. Moreover, for control of enzymatic treatment, CB-staining was also only performed after a pre-fixation in glutaraldehyde with or without an intermediate step of sham digestion.…”
Section: Discussionmentioning
confidence: 99%